Teaching and Learning Mathematical Modelling: Approaches and Developments from German Speaking Countries - Greefrath, Gilbert; Vorhölter, Katrin (Cham Springer Nature, 2016)
Mathematics Education; Teaching; Learning and Instruction
English
Keywords: Education; Mathematics & science; Mathematics Education; Teaching; Learning and Instruction